An Introduction to Ethics in Robotics and AI - Bartneck, Christoph; Lütge, Christoph; Wagner, Alan; Welsh, Sean (Springer Nature, 2021)
This open access book introduces the reader to the foundations of AI and ethics. It discusses issues of trust, responsibility, liability, privacy and risk. It focuses on the interaction between people and the AI systems and Robotics they use. Designed to be accessible for a broad audience, reading this book does not require prerequisite technical, legal or philosophical expertise. Throughout, the authors use examples to illustrate the issues at hand and conclude the book with a discussion on the application areas of AI and Robotics, in particular autonomous vehicles, automatic weapon systems and biased algorithms. A list of questions and further readings is also included for students willing to explore the topic further.
English
Keywords: Ethics & moral philosophy; Artificial intelligence; Psychology; Engineering Ethics; Robotics; Applied Psychology; Moral Philosophy and Applied Ethics; Behavioral Sciences and Psychology; AI and ethics; ethics and robotics; descriptive ethics; relationship between ethics and law; machine ethics; machine meta-ethics; machine normative ethics; types of AI systems; strong and weak AI; challenges of AI; Open Access; Ethics & moral philosophy; Technology: general issues; Artificial intelligence; Psychology